Assessment of d.c. traction stray currents effects on nearby pipelines. Issue 4 (4th July 2016) - Machczynski, Wojciech; Budnik, Krzysztof; Szymenderski, Jan
Abstract : Purpose: – dc electrified traction systems are a potential source of stray currents. The purpose of this paper is to evaluate the harmful effects (electrolytic corrosion) that an electrified railway has on nearby earth return circuits (e.g. pipelines). Design/methodology/approach: – The electric circuit approach, based on the earth return circuit theory, to model stray currents interference on extended structures is presented. An exact method of calculation is applicable to any dc railway system in which tracks can be represented by a single earth-return circuit (equivalent rail) with current energization. In the approximate method, the equivalent rail with current energization is modeled as a large multinode electrical equivalent circuit with lumped parameters. The circuit is a chain of basic circuits, which are equivalents of homogenous sections of the rail. The electrode kinetics (polarization phenomenon) is taken into account in the model developed. Findings: – Formulas in partially closed forms are derived applicable to the analysis of currents and potentials along a pipeline laid in the proximity with railway tracks. The attempt is undertaken, to incorporate the electrode kinetics into the simulation model in which the polarization phenomenon (Tafel equation) is modeled by a non-linear voltage source with source voltage being iteratively calculated. The polarization potential along the affected pipeline can be determined. Originality/value: – The pipeline electrochemical response (polarization behavior – non-linear phenomenon on the interface metal-soil electrolyte) to the dc stray currents interference is innovative incorporated into the simulation model with lumped parameters using the iterative process.